Dispositional gratitude moderates the association between socioeconomic status and interleukin-6 - HARTANTO, Andree (Institutional Knowledge at Singapore Management University, 2019)
Socioeconomic disparities in health are prevalent and growing in importance as a concern amongacademics, policymakers, and the general public. However, psychological resources that can narrowsuch disparities have not been well-examined. The current study examined the moderating role ofdispositional gratitude in the relationship between socioeconomic status (SES) and infammationrisk as an index of health. Participants consisted of 1,054 midlife adults from the biomarker projectof the Midlife in the United States. Infammation risk was measured by interleukin-6 biomarker andSES was operationalized by education attainment and income. We found that dispositional gratitudesignifcantly moderated the relationships between SES and interleukin-6. Among individuals withlow dispositional gratitude, higher SES was signifcantly associated with lower levels of interleukin-6.However, the association between SES and interleukin-6 was not signifcant among individuals withhigh dispositional gratitude. More importantly, the fndings remained robust after controlling fordemographic characteristics, health status, health behaviours, and personality traits. Our fndingssuggest that gratitude may serve as an important psychological resource in attenuating health-relatedrisk from socioeconomic stressors.